2016 IEEE Uttar Pradesh Section International Conference on Electrical, Computer and Electronics Engineering (UPCON) 2016
DOI: 10.1109/upcon.2016.7894725
|View full text |Cite
|
Sign up to set email alerts
|

FogGIS: Fog Computing for geospatial big data analytics

Abstract: Abstract-Cloud Geographic Information Systems (GIS) has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Fog framework added privacy benefit where we process the data locally at Fog devices and send only the analysis results to cloud layer. Figure 1 (b) shows the Conceptual diagram of the fog framework for geospatial health data storage and analysis [4,10,11]. From the above conceptual diagram of cloud and fog framework, it observed that the geospatial data as a key components for data analysis in cloud layer [9,8].…”
Section: Related Work 21 Fog and Cloud Computingmentioning
confidence: 98%
See 1 more Smart Citation
“…Fog framework added privacy benefit where we process the data locally at Fog devices and send only the analysis results to cloud layer. Figure 1 (b) shows the Conceptual diagram of the fog framework for geospatial health data storage and analysis [4,10,11]. From the above conceptual diagram of cloud and fog framework, it observed that the geospatial data as a key components for data analysis in cloud layer [9,8].…”
Section: Related Work 21 Fog and Cloud Computingmentioning
confidence: 98%
“…Disease phenomena are strongly associated with geospatial and related temporal factors. For tackling these situation, Cloud framework has provided dynamic and real-time way to represent disease information through the maps on common browsers [2] [4]. So for sharing and analysis of health data in secure way, we have to concentrate with various security issues which has discussed in next section.…”
Section: Geohealth Big Datamentioning
confidence: 99%
“…[49,9]. devices such as smart phones and mobile GIS interfaces [9,67,47,41,12,54]. We consider this technology for integrating it with health GIS for better management of geospatial health data.…”
Section: Fog Computingmentioning
confidence: 99%
“…It is not a new thing, since it has been used from decades to communicate information in a better and easier way [25]. A vast amount of data is generated every day, only 20% of this is structed rest is all unstructured data, visualizing data helps in exploring and analyzing data in easier way as it helps in understanding data, finding correlations, finding general trends in data etc.…”
Section: Big Data Visualizationmentioning
confidence: 99%